Sumber-Sumber Ilmu Pengetahuan dalam Al Qur’an dan Hadits - Sayid Qutub (Bina Nusantara University, 2011)
From the beginning, Islam had given gratitude towards knowledge. One enlightenment that Islam has brought to humanity is scientific thinking refered to Alquran and Hadits. The awareness of Muslim scientist based on Alquran and Hadits produced the biggest achievement of knowledge. Other characteristics taught by Alquran and Hadits to the Muslims are open-minded, that allowed them to get knowledge from other civilization with no justification. The purpose of this article is to establish understanding of Alquran and Hadits in thematic analysis, especially about knowledge. This article is written based on literature review about related knowledge and the interpretation of Alquran and Hadits (tafsir). It is known that there is no standalone or separated knowledge from Islamic epistemology; the knowledge is the description of devine affirmation, absolute fact. This article is expected to be a filter in anticipating negative influence from knowledge and technology development.